Meningkatkan Hasil Belajar Siswa dengan Menggunakan Model Problem Beased Learning Pada Materi Dinamika Litosfer dan Dampaknya Terhadap Kehidupan Kelas X SMA Negeri 1 Kontunaga - Askar Widodo; Sitti Kasmiati; Andrias Andrias (Jurnal Penelitian Pendidikan Geografi, 2025)
Senior High School 1 Kontunaga is one of the schools located in Kontunaga District, Muna Regency which has low student Geography learning outcomes. The low learning outcomes are caused by teachers only using ordinary learning methods so that students feel bored and less interested in the learning process. This study aims to: 1) determine student learning activities; 2) determine teacher teaching activities; and 3) determine the improvement in Geography learning outcomes of class X IPS students at Senior High School 1 Kontunaga by applying the Problem Based Learning (PBL) learning model on the material Lithosphere Dynamics and Its Impact on Life. This type of research is Classroom Action Research. The results of the study showed: 1) the average score obtained from student activities was 2.1 with a sufficient category and increased to 3.6 with a good category; 2) teacher teaching activities obtained a score of 2.7 with a sufficient category increasing to 3.5 with a good category; and 3) the Geography learning outcomes of class X students of SMA Negeri 1 Kontunaga obtained an average learning outcome of 63% increasing to 87%. The PBL model is considered to be able to improve student learning activities, teacher teaching activities, and student learning outcomes.